Hydrothermal pretreatment: A sustainable approach to biohydrogen production from palm oil mill effluent - Zainal B.S.; Yu K.L.; Mohamed H.; Ong H.C.; Mahlia T.M.I. (Elsevier Ltd, 2025)
Palm oil mill effluent (POME) poses a significant environmental challenge in Malaysia, necessitating effective wastewater management. This study explores innovative methods for treating POME, focusing on sustainable biohydrogen production. Therefore, this research aims to investigate the optimum conditions for substrate pretreatment using hydrothermal, a vital step in the bioconversion of biomass to hydrogen. Biohydrogen production was determined through a dark fermentation process using a Box-Behnken design to optimise the efficiency of substrate pretreatment temperature, holding time and POME percentage. This study found that the optimal conditions for hydrothermal pretreatment were achieved at 212 C, with a 30 min holding time, and utilising 100 % POME. Under these conditions, the study performed a notable 78 % of chemical oxygen demand removal efficiency (CODrem.eff). Additionally, the process yielded 242 ml of total biohydrogen volume, with the final pH stabilised at 6.7. Microbial analysis showed that Chloroflexota phylum is dominant in the optimum sample, with the presence of T78 and Clostridia species. This research pioneers the hydrothermal pretreatment method for biohydrogen production, demonstrating its effectiveness in enhancing CODrem.eff and hydrogen yield, thus providing a sustainable solution to palm oil waste management. ? 2024 Elsevier Ltd